Physician-initiated clinical study of limb ulcers treated with a functional peptide, SR-0379: from discovery to a randomized, double-blind, placebo-controlled trial. (December 2018) - Nakagami, Hironori; Sugimoto, Ken; Ishikawa, Takahiro; Fujimoto, Taku; Yamaoka, Toshifumi; Hayashi, Misa; Kiyohara, Eiji; Ando, Hiroshi; Terabe, Yuta; Takami, Yoichi; Yamamoto, Koichi; Takeya, Yasushi; et al.
Abstract SR-0379 is a functional peptide that has wound healing effect with anti-microbial action, making it an ideal drug to prevent infection. To evaluate the safety, efficacy, and pharmacokinetics of SR-0379 for the treatment of leg ulcers, a physician-initiated, phase I/IIa, first-in-patient clinical study was designed. A multi-center, double-blind, randomized clinical study was conducted from October 2015 to September 2016. The inclusion criteria for leg ulcers were (1) diabetes or critical limb ischemia and (2) wound size <6 cm in diameter. Twelve patients were randomized into four groups and administered 0.02%, 0.1%, or 0.5% SR-0379 or placebo treatment on skin ulcers once per day for 28 days. Efficiency was evaluated by determining the rate of wound size reduction as a primary endpoint at 4 weeks after the first treatment compared with the pre-treatment wound size. As a secondary endpoint, the DESIGN-R score index, time to wound closure, and the 50% wound size reduction ratio were also evaluated. The safety of SR-0379 was evaluated during the study period. In the evaluation of efficiency, the skin ulcer reduction rates at the last evaluation were 44.73% for the 0.02% SR-0379 group, 68.25% for the 0.1% group, and 71.61% for the 0.5% group, compared with 9.95% for the placebo group. Six adverse events were reported in four patients, of which one occurred in the placebo group, and causal relationships to study drugs were denied for all six events. Treatment with SR-0379 for chronic leg ulcers was safe, well tolerated, and effective. Dermatology: peptide drug development for skin ulcers Chronic leg ulcers result in substantial impairment of patient quality of life with a socioeconomic impact both in terms of medical care and missed work days. A teams led by Hironori Nakagami at Osaka University originally identified a functional peptide, SR-0379, and evaluated the safety and efficacy of SR-0379 for the treatment of leg ulcers in a physician-initiated, first-in-patient, a multi-center, double-blind, randomized clinical study. In the evaluation of efficiency, the skin ulcer reduction rates were improved for the SR-0379 treated groups in a dose-dependent manner, compared for the placebo group with no causal adverse events. Since treatment with SR-0379 for chronic leg ulcers was safe, well tolerated, and effective in this initial clinical trial, the clinical trial on next stage will be designed toward peptide drug development.